Legal Analysis Related to the Application of Artificial Intelligence in Notarial Practice - Mariyam, Mariyam; Rahmawati, Umi; Nur Sofia Madani, Nadea; Fifin Nazilah, Fanis; Ulhaq Mahfudzoh, Dhiya’ (Journal of Law, Politic and Humanities, 2024)
In the era of globalization and rapid technological development, the implementation of artificial intelligence (AI) has become an unavoidable phenomenon in various fields, including law and notary. AI offers significant potential to improve efficiency and accuracy in notarial practice, but also poses various juridical challenges. Notaries are recognized as trusted parties by the public to ensure the authenticity of a deed and prevent legal violations. Although AI can assist in administrative tasks and data analysis, its implementation must consider juridical aspects such as legal liability, personal data protection, and document authenticity. In facing the fourth industrial revolution, notaries need to update their knowledge and skills and maintain the relevance of civil law. Collaboration between human and artificial intelligence is required to achieve better results without sacrificing principles of justice and legal authenticity.